2016
DOI: 10.1186/s12936-016-1192-y
|View full text |Cite
|
Sign up to set email alerts
|

Predicting factors for malaria re-introduction: an applied model in an elimination setting to prevent malaria outbreaks

Abstract: BackgroundMalaria re-introduction is a challenge in elimination settings. To prevent re-introduction, receptivity, vulnerability, and health system capacity of foci should be monitored using appropriate tools. This study aimed to design an applicable model to monitor predicting factors of re-introduction of malaria in highly prone areas.MethodsThis exploratory, descriptive study was conducted in a pre-elimination setting with a high-risk of malaria transmission re-introduction. By using nominal group technique… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 22 publications
2
20
0
Order By: Relevance
“…Low-density gametocytes can readily infect Anopheles, even at sub-microscopical levels [37,38]. Secondary transmission, originating from imported malaria, is often reported in GCC countries in areas where the Anopheles vector is present and a favorable ecological habitat prevails [3,39] Although the resumption of endemic transmission in GCC countries is unlikely, the high rate of imported malaria can readily seed outbreaks in receptive areas, if vector control wanes [3].…”
Section: Discussionmentioning
confidence: 99%
“…Low-density gametocytes can readily infect Anopheles, even at sub-microscopical levels [37,38]. Secondary transmission, originating from imported malaria, is often reported in GCC countries in areas where the Anopheles vector is present and a favorable ecological habitat prevails [3,39] Although the resumption of endemic transmission in GCC countries is unlikely, the high rate of imported malaria can readily seed outbreaks in receptive areas, if vector control wanes [3].…”
Section: Discussionmentioning
confidence: 99%
“…In order to direct interventions, models must incorporate both the risk of importation and the risk for the reestablishment of local transmission [ 165 173 ]. The risk of malaria transmission reestablishment can be measured as a function of selected host, vector, and environmental data [ 156 , 170 , 171 , 174 ].…”
Section: Opportunitiesmentioning
confidence: 99%
“…In order to direct interventions, models must incorporate both the risk of importation and the risk for the reestablishment of local transmission [ 165 173 ]. The risk of malaria transmission reestablishment can be measured as a function of selected host, vector, and environmental data [ 156 , 170 , 171 , 174 ]. For example, measures might include human use of insecticide-treated bed nets or indoor residual spraying, mosquito habitat suitability and its link to abundance, and climatic conditions (e.g., temperature, rainfall, and vegetation index measures) that support or accelerate vector and parasite development.…”
Section: Opportunitiesmentioning
confidence: 99%
“…Resurgence of malaria is often associated with imported infections and/or P. vivax relapsing infections in areas that remain highly receptive to malaria [13][14][15][16]. Studies have demonstrated the usefulness of spatially referenced entomological data to characterise the heterogeneity of malaria receptivity in areas approaching elimination to prevent outbreaks in the future [17][18][19].…”
Section: Introductionmentioning
confidence: 99%